Response to COVID-19 in the Central African Republic: Coping Strategies Combined With China’s Experience - Gou, Qiheng; Zhu, Fubin; Xie, Keqi; Li, Yiping; Xie, Yuxin (International Journal of Public Health, 2022)
The weak health system, domestic political unrest, poverty, and many other factors in the Central Republic (CAR) have left the country underprepared for the COVID-19 pandemic, resulting in a greater health threat to the entire country. Rapid measures must therefore be taken to prevent the further spread of COVID-19. The valuable experience and lessons learned from China's successful response to the pandemic may be of great benefit to the CAR. Here, we aim to analyze how far Chinese COVID measures can be transferred to the context of the CAR and why the specific context of the CAR also requires international help and hence cannot simply copy China’s strategy.